Determinants of NEET in Matrilineal Province of West Sumatra During the Covid-19 Pandemic - Hella Citra; Febria Sri Artika (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
NEET (Not in Education, Employment, or Training)is one of the Sustainable Development Goals (SDGs) indicators used to assess the level of vulnerability of the young population aged 15-24 in terms of unemployment, school dropout, and labor-market despair. According to BPS data, 195,380 people in West Sumatra Province (20.5 percent) became NEET in 2020. Nationally, West Sumatra's NEET rate is ranked the 13th highest. This study aims to determine the general description and determinants that cause a person to have the opportunity to become a NEET in West Sumatra using Sakernas data in 2020. The analysis method used is descriptive statistics and inferential statistics with a binary logistic regression model. The results showed that, with a 99 percent confidence level, the variables that significantly affect a person's status as NEET are age, disability, marital status, education, skills, work experience, education of the head of the household, number of children, presence of toddlers or elderly, presence of working household members, and the perceived impact of COVID-19. People with disabilities are six times more at risk of becoming NEET than those without disabilities. Meanwhile, gender status and location of residence do not affect a person's status as a NEET. In contrast to other provinces where women are more likely to become NEET, West Sumatera's unique matrilineal system means that gender has no bearing on a person's NEET status.